2022
DOI: 10.1001/jamacardio.2022.3736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dapagliflozin on Cause-Specific Mortality in Patients With Heart Failure Across the Spectrum of Ejection Fraction

Abstract: ImportanceIn 2 trials enrolling patients with heart failure (HF) across the spectrum of ejection fraction (EF), dapagliflozin has been shown to reduce the rate of the composite of worsening HF events or death from cardiovascular (CV) causes.ObjectiveTo examine the effects of dapagliflozin on cause-specific CV and non-CV mortality across the spectrum of EF.Design, Setting, and ParticipantsThis was a participant-level, pooled, prespecified secondary analysis of data from the Dapagliflozin and Prevention of Adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 14 publications
1
26
1
2
Order By: Relevance
“…Conversely, cardiovascular death was not significantly less frequent with SGLT2i than with placebo. This is not surprising, as non-cardiovascular death is predominant in HFpEF 30 and the influence of SGLT2i on mortality is limited 31 . Interestingly, it has recently been suggested that SGLT2i may affect the risk of sudden cardiac death in HFpEF 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, cardiovascular death was not significantly less frequent with SGLT2i than with placebo. This is not surprising, as non-cardiovascular death is predominant in HFpEF 30 and the influence of SGLT2i on mortality is limited 31 . Interestingly, it has recently been suggested that SGLT2i may affect the risk of sudden cardiac death in HFpEF 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as non-cardiovascular death is predominant in HFpEF 30 and the influence of SGLT2i on mortality is limited. 31 Interestingly, it has recently been suggested that SGLT2i may affect the risk of sudden cardiac death in HFpEF. 32 As this meta-analysis was based on aggregate data with no distinction of the modes of death, we cannot address this observation.…”
Section: Discussionmentioning
confidence: 99%
“…24 The limitations of LVEF in categorizing HF are well-recognized 28 , and several therapies have been proven to be of benefit regardless of LVEF. 29,30 Recent changes in the nomenclature of HF subtype classification 31 have signaled a reconsideration of the determinants of patient eligibility for HF therapies. The results of our cluster analysis align with this position by demonstrating the importance of the underlying pathophysiological features of HF.…”
Section: Discussionmentioning
confidence: 99%
“…61 A major recent change has been sodium-glucose cotransporter 2 inhibitors (eg, empagliflozin, dapagliflozin), which improve outcomes in both HFpEF and HFrEF. 61,65,66 Preexisting HF is a recognized risk factor for postoperative mortality and morbidity. 67 The associated risks of 90-day mortality are even higher for individuals with symptomatic versus asymptomatic HF, and individuals with progressively reduced systolic dysfunction.…”
Section: Hfmentioning
confidence: 99%
“…Importantly, most medical therapy for improving morbidity and mortality in HF has only shown efficacy in HFrEF, including ACE inhibitors, ARBs, and beta-blockers 61. A major recent change has been sodium-glucose cotransporter 2 inhibitors (eg, empagliflozin, dapagliflozin), which improve outcomes in both HFpEF and HFrEF 61,65,66…”
Section: Hfmentioning
confidence: 99%